Helicobacter pylori seropositivity in subjects with acute myocardial infarction. Issue 4 (October 1996) - Rathbone, B.; Martin, D.; Stephens, J.; Thompson, J. R.; Samani, N. J.
Abstract : OBJECTIVE: To determine whether Helicobacter pylori infection increases the risk of myocardial infarction. DESIGN: Case-control study. SETTING: University teaching hospital. METHODS: Serological evidence of H pylori infection was determined in 342 consecutive patients with acute myocardial infarction admitted into the coronary care unit and in 236 population-based controls recruited from visitors to patients on medical and surgical wards. RESULTS: 206/342 (60.2%) of cases were H pylori positive compared with 132/236 (55.9%) of controls (P = 0.30). Age and sex stratified odds ratio for myocardial infarction associated with H pylori seropositivity was 1.05 (95% CI 0.7 to 1.53, P = 0.87) and this remained non-significant (P = 0.46) when other risk factors for ischaemic heart disease were taken into account using logistic regression analysis. H pylori seropositivity was not associated with several coronary risk factors in either cases or controls. CONCLUSION: No increase was found in H pylori seropositivity in subjects with acute myocardial infarction. This suggests that previous H pylori infection is not a major risk factor for acute myocardial infarction.